Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Sun, Cui-Ci; Yue, Wei-Zhong; Wang, You-Shao; He, Wei-Hong; Hong, Yi-Guo; Sun, Fu-Lin; Cheng, Hao; Wu, Mei-Lin; Jiang, Zhao-Yu; Jiao, Fei; Wang, Yu-Tu (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSPcolor concentrations (CSP concentration determined spectrophotometrically) were 73.7 to 685.3 μg BSA eq L−1 (μg Bovine serum albumin (BSA) equivalent liter-1) in August 2016 and 100.6 to 396.4 μg BSA eq L−1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (＜5) , and declined from the river to the middle estuary by 80% in the wet season and 55. 6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a/CSPcolor showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6× 106 mol N d−1. These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.